Climate finance and deforestation: an empirical analysis of the forest transition curve in sub-Sahara Africa. (12th February 2022) - Doku, Isaac; Ncwadi, Ronney; Phiri, Andrew
The aim of this study is to investigate the impact of climate finance on deforestation among 44 sub-Sahara African countries for the period of 2006-2017 and testing whether Forest Transition Curve (FTC) exists in the region. System-GMM is employed as the main estimation technique and panel quantile regressions are employed to test sensitivity of the results. Overall, our findings do not offer support for the conventional FTC, but indicated that forest transition curve is rather U-shaped for all countries in sub-Sahara Africa in support of the climate finance effect (i.e. climfin effect). Population growth and agricultural land use have been found to be the major drivers of deforestation whilst most governance indicators showed adverse impact on deforestation. Consequentially, the study recommends the need to strengthen governance indicators such as control of corruption and regulatory quality to ensure that climate finance reaches target destination of environmental conservation.